Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pendidikan, Pemuda Dan Olahraga Kota Pariaman - Sumiati, Sumiati; Ariadi, Teguh (CV. ITTC INDONESIA, 2023)
This study aims to analyze the effect of work discipline and work environment on employee performance at the Pariaman City Education, Youth and Sports Office. This study uses quantitative methods. The population is the employees of the Pariaman City Education, Youth and Sports Office, as many as 40 respondents and a sample of 40 respondents, the sampling technique is the Saturated Sampling Technique where all the population is sampled. Data analysis used Multiple Linear Regression Analysis using the SPSS 26 application. The results showed that Work Discipline had a positive and significant effect on Employee Performance at the Education, Youth and Sports Office, and the work environment had a positive and significant impact on Employee Performance at the Education Office, Pariaman City Youth and Sports.